Physical activity levels, blood pressure status, and their correlates among secretariat officers: a cross-sectional study from Bangladesh - Ghosh, Chitra; Biswas, Mukul; Ghosh, Bikarna Kumar; Ghosh, Gitanjali (International Journal of Research in Medical Sciences, 2025)
Background: Hypertension remains a major global health concern, with sedentary lifestyles contributing significantly to its prevalence. Secretariat officers, due to their desk-bound occupations, face an increased risk of hypertension. Physical activity is associated with blood pressure regulation, but little information is available on its association with government employees in Bangladesh. This study aimed to assess the physical activity level, blood pressure status and their association among secretariat officers in Bangladesh. Methods: A descriptive cross-sectional study was conducted from January 1 to December 31, 2020 among 255 officers of the Bangladesh Secretariat’s Information Communication Technology and Public-Private Partnership ministries. Data assessment included structured questionnaires, physical measurements (BMI, blood pressure), and the international physical activity questionnaire (IPAQ). Blood pressure was grouped according to standard guidelines, and physical activity was classified as low, moderate, and high. SPSS was used to perform statistical analyses, applying chi-square and t-tests to assess significance. Results: The mean age of the participants was 35.55±6.9 years, with 76.9% male. 25.5% of the respondents were hypertensive, and 11.8% were prehypertensive. 49% of participants were sedentary, 30% met guidelines for physical activity, and 21% remained just below the mark. There was a significant association between overweight and obesity (p=0.00) and hypertension, but no significant association between physical activity levels and blood pressure (p=0.226). Conclusions: Hypertension remains common, even among those with moderate to high levels of physical activity, and other contributing factors, such as occupational stress and BMI, must be taken into account. Targeted interventions, such as workplace wellness programs and periodic screening, are recommended to mitigate hypertension risks among secretariat officers.